Modelling and simulation in drug absorption processes - Dokoumetzidis, A.; Valsami, G.; Macheras, P. (XENOBIOTICA, 2007)
Drug absorption is a complex process dependent upon drug properties such as solubility and permeability, formulation factors, and physiological variables including regional permeability differences, pH, luminal and mucosal enzymes, and intestinal motility, among others. Despite this complexity, various qualitative and quantitative approaches have been proposed for the estimation of oral drug absorption. These approaches are reviewed in this article with particular emphasis on drug dissolution modelling, dynamic systems for oral absorption and absorption models based on structure. The regulatory aspects of oral drug absorption and in particular the biopharmaceutic classification of drugs are also discussed. Models for drug dissolution and release describe adequately the in vitro data, and models for oral drug absorption provide reasonable results. The development of in vitro-in vivo correlations based on the official compendia specifications are facilitated using commercial computer packages.
Keywords: Dissolution; drug absorption; intestinal transit; Permeability; Solubility